Anthologizing Sir Samuel Ferguson: Literature, History, Politics - Jędrzejewski, Jan (Text Matters: A Journal of Literature, Theory and Culture, 2014)
Although Sir Samuel Ferguson is generally recognized as one of the key figures of mid-nineteenth-century Irish literature, there has been no major edition of his poems since 1916, as a result of which his work tends to be known to the general reader through selections published in anthologies. The essay analyzes the selections of Ferguson’s work in anthologies of Irish literature published between 1895 and 2010 in an attempt to assess the impact of the cultural dynamics of twentieth-century Ireland on the interpretation of Ferguson’s achievement as a poet. The evidence collected demonstrates that the image of Ferguson perpetuated by most twentiethcentury anthologists, most of them Hibernocentric in approach, was that of a respectable if rather old-fashioned Romantic nationalist antiquarian, whose work focused primarily on familiarizing the Victorian reader with the ancient myths and traditions of Ireland. This interpretation of Ferguson’s achievement, motivated, it is argued, by the predominantly nationalist agenda of modern Ireland’s cultural establishment, has largely marginalized the other side of Ferguson—a political thinker committed to the unionist cause and vehemently opposed to the violence perpetrated by the emergent Irish republican movement and culminating in the Phoenix Park murders of 1882, which formed the subject of two of Ferguson’s most powerful late poems, “At the Polo-Ground” and “In Carey’s Footsteps.”